2020
DOI: 10.1111/acps.13241
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure and connectivity in patients with obsessive‐compulsive disorder and their unaffected siblings

Abstract: ObjectiveWe aimed to examine white matter microstructure and connectivity in individuals with obsessive–compulsive disorder (OCD) and their unaffected siblings, relative to healthy controls.MethodsDiffusion‐weighted magnetic resonance imaging (dMRI) scans were acquired in 30 patients with OCD, 21 unaffected siblings, and 31 controls. We examined white matter microstructure using measures of fractional anisotropy (FA), radial diffusivity (RD), and axial diffusivity (AD). Structural networks were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Compared with HCs, this study showed decreased FA in several WM tracts involving the corpus callosum, cingulum, and inferior fronto-occipital fasciculus, among others, in patients with OCD. Our results are consistent with previous reports( Dikmeer et al, 2021 , Gan et al, 2017 , Piras et al, 2021 ) and provide evidence for the notion that the pathophysiology of OCD is not limited to the CSTC circuits but also involves abnormalities in more extended brain regions( Anticevic et al, 2014 ). The decreases in WM FA could be the microstructural basis for the disrupted structural and functional connectivity in distributed brain networks in OCD.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Compared with HCs, this study showed decreased FA in several WM tracts involving the corpus callosum, cingulum, and inferior fronto-occipital fasciculus, among others, in patients with OCD. Our results are consistent with previous reports( Dikmeer et al, 2021 , Gan et al, 2017 , Piras et al, 2021 ) and provide evidence for the notion that the pathophysiology of OCD is not limited to the CSTC circuits but also involves abnormalities in more extended brain regions( Anticevic et al, 2014 ). The decreases in WM FA could be the microstructural basis for the disrupted structural and functional connectivity in distributed brain networks in OCD.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, previous imaging genetic studies have reported myelin-related white matter (WM) abnormalities in OCD( Atmaca et al, 2010 , Stewart et al, 2007 , Zai et al, 2021 ). Diffusion tensor imaging (DTI) studies have also found significant WM microstructural changes in OCD, suggesting disrupted WM myelin integrity in this disorder( Dikmeer et al, 2021 , Gan et al, 2017 , Piras et al, 2021 , Saito et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches found that the (functional) hypoconnectivity in frontal-striatal areas in both patients and their clinically asymptomatic relatives may serve as a biomarker for OCD ( Vaghi et al, 2017 , Chamberlain et al, 2008 ). Moreover, previous neuroimaging studies have revealed network abnormalities, such as atypical small-world properties ( Peng et al, 2013 ) and altered white matter ( Menzies et al, 2008 , Dikmeer et al, 2021 ), in both OCD patients and their FDR. However, whether the basis for information dissemination in those brain networks, namely the rich club, can be treated as a putative vulnerability biomarker, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The present study preliminarily investigated rich‐club organization in a small group of unaffected siblings. Generally, neuroimaging markers of anomaly present in both patients and unaffected first‐degree relatives, but not in healthy controls, are good candidates, and potential endophenotypes have been identified in measures of white‐matter microstructure (Dikmeer et al, 2021; Fan et al, 2016; Menzies et al, 2008), network properties (Peng et al, 2014) and functional patterns of dysconnectivity (Chamberlain et al, 2008; Peng et al, 2014; Vaghi et al, 2017). Research on whether rich‐club organization could be considered as such is limited, with only one study reporting intermediate levels of rich‐club connectivity in unaffected siblings (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given (Dikmeer et al, 2021;Menzies et al, 2008), network properties and functional patterns of dysconnectivity (Chamberlain et al, 2008;Vaghi et al, 2017). Research on whether rich-club organization could be considered as such is limited, with only one study reporting intermediate levels of rich-club connectivity in unaffected siblings (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%